School Nursing Guide for student health promotion: construction and validity - Emanoel Avelar Muniz; Maria Veraci Oliveira Queiroz; Patrícia Neyva da Costa Pinheiro; Maria Rocineide Ferreira da Silva; Thereza Maria Magalhães Moreira; Eliany Nazaré Oliveira; Isabelline Freitas Dantas Paiva de Almeida; Valter Cordeiro Barbosa Filho (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to describe the process of construction and validity of a School Nursing Guide for student health promotion. Methods: a methodological study, carried out from February to December 2021, composed of Convergent Care Research based on Pender's Health Promotion Model. Based on the literature and dialogue with 11 nurses in the seven online focus groups, actions were constructed. Subsequently, 24 judges assessed content and appearance. Results: the guide proposes strategies for developing school nursing practices focusing on health promotion. The Appearance Validity Index ranged from 0.63 to 1.0, and the total was 0.84. The Content Validity Index ranged from 0.95 to 1.0, and the total was 0.997. Conclusions: the guide incorporated the needs of young people recognized by professionals, and the assessment phase confirms its validity, and can be used in the context of practice with young people.